The applied program means and training of scientific and technical texts translators - D A Alferova (Polylinguality and Transcultural Practices, 2008)
The information technologies application is an important aspect in the potential realisation of a scientific and technical texts translators. The future translators being familiar with such technologies and their being able to apply them when translating the scientific and technical texts will improve their professional training in the professional communication field.